Certified Teacher is not enough as a Professional Teacher: Between Theory and Practice - Eko Suhartoyo; Diah Retno Widowati (STKIP PGRI Tulungagung, 2018)
Teachers play important role in education. As the agent of education, teachers do not simply deliver the knowledge to students. Teachers are those who conduct the learning in the classroom. In developing national education, having qualified teachers is undeniable need. This considers the important role of teachers in the process of education. Qualified teachers refer to those who have standard competence and professionalism. This paper described the theory of teacher certification and the practice in educational world and what certification do to teachers today. The researchers delivered questionnaires to 50 authoritative teacher in order to know the activity during PLPG.